Intelligent Control and Computer Engineering - Ao, Sio-Long (Springer, 2012)
A large international conference on Advances in Intelligent Control and Computer Engineering was held in Hong Kong, March 17-19, 2010, under the auspices of the International MultiConference of Engineers and Computer Scientists (IMECS 2010).